Pengaruh Pengalaman Pelanggan dan Kepercayaan Pelanggan terhadap Loyalitas Pelanggan dengan Nilai yang Dirasakan (Perceived Value) sebagai Variabel Mediasi pada Usaha Kecil di Kabupaten Muaro Jambi - Ingepuri, Pebriana; Lubis, Tona Aurora; Solikhin, Agus (Universitas Batanghari Jambi, 2025)
This research aims to examine the influence of customer experience and customer trust on customer loyalty with perceived value as a mediating variable in Small Businesses in Muaro Jambi Regency. This type of research is quantitative with an explanatory approach. Data collection was carried out by distributing questionnaires to 190 respondents who were small business customers in Muaro Jambi Regency. Data analysis uses the partial least squares (PLS) method. The research results show that customer experience and customer trust have a positive and significant effect on customer loyalty. In addition, perceived value is proven to mediate the influence between customer experience and customer trust on customer loyalty. These findings confirm that sensory elements in customer experience as well as service reliability in building trust play an important role in increasing customer loyalty. By providing high perceived value, small businesses can strengthen relationships with customers, increase competitive advantage, and drive sustainable business growth.